Ciphering key of chaos image encryption - Mazleena Salleh 333705; Subariah Ibrahim; Ismail Fauzi Isnin 435417; International Conference on Artificial Intelligence in Engineering and Technology (2002 : Universiti Malaysia Sabah, Kota Kinabalu) 468408 (Skudai : Universiti Teknologi Malaysia, 2002)
40